2015
DOI: 10.3109/08923973.2014.999160
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory properties of shark cartilage supplement

Abstract: The erosion and breakdown of cartilage is generally recognized to be an integral manifestation of arthritic disease, which is often accompanied by the development and progression of inflammation associated with it. Commercial shark cartilage (SC) is a popular dietary supplement taken for the prevention and/or control of chronic disease, including arthritis. The efficacy of SC in maintaining joint health remains questionable; there is a lack of sufficient reliable information on its effect on immunocompetent ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The skeletons of sharks and other elasmobranch species are composed of cartilage, which is a connective tissue rich in proteins such as collagens and proteoglycans (Sim, et al, 2007). Shark cartilage has been investigated as a possible treatment for numerous medical conditions, including arthritis and cancer (Merly & Smith, 2015;Mondo, et al, 2014;Sim, et al, 2007). Due to its purported health benefits, shark cartilage is widely used as a dietary supplement.…”
Section: Introductionmentioning
confidence: 99%
“…The skeletons of sharks and other elasmobranch species are composed of cartilage, which is a connective tissue rich in proteins such as collagens and proteoglycans (Sim, et al, 2007). Shark cartilage has been investigated as a possible treatment for numerous medical conditions, including arthritis and cancer (Merly & Smith, 2015;Mondo, et al, 2014;Sim, et al, 2007). Due to its purported health benefits, shark cartilage is widely used as a dietary supplement.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplements containing shark cartilage, the health benefits of which are purportedly bolstered by traditional Chinese medicine claims, have gained popularity in western nations. However, the U.S. Food and Drug Administration (FDA) has been unable to confirm any proclaimed benefits [16] and available reports of health benefits are questionable [17]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, the Florida Department of Health (FDOH) advises that people should not eat sharks greater than ~109 cm and further recommends that children and pregnant woman not eat any shark meat [23]. Moreover, recent studies have reported that commercial shark cartilage supplements contain pro-inflammatory compounds that could pose health risks for consumers, especially those with inflammatory diseases [17]. …”
Section: Introductionmentioning
confidence: 99%